2004
DOI: 10.1074/jbc.m409155200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Translesion DNA Synthesis across a Benzo[a]pyrene-Guanine Adduct in Mammalian Cells

Abstract: Replication across unrepaired DNA lesions in mammalian cells is effected primarily by specialized, low fidelity DNA polymerases. We studied translesion DNA synthesis (TLS) across a benzo[a]pyrene-guanine (BP-G) adduct, a major mutagenic DNA lesion generated by tobacco smoke. This was done using a quantitative assay that measures TLS indirectly, by measuring the recovery of gapped plasmids transfected into cultured mammalian cells. Analysis of PolK ؉/؉ mouse embryo fibroblasts (MEFs) showed that TLS across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(190 citation statements)
references
References 53 publications
10
179
1
Order By: Relevance
“…The minor-groove lesion positioning is suggested to be relevant to other Y family DNA polymerases of the DinB branch, including the human homolog Pol κ [22]. The DinB polymerases seem to have a special role in bypassing N 2 -dG lesions [38], with higher efficiency and accuracy than other DNA polymerases in cellular [39] and in vitro environments [40,41].…”
Section: Dpo4 Produces Mismatch and Frameshift Mutations At Bp-derivementioning
confidence: 98%
“…The minor-groove lesion positioning is suggested to be relevant to other Y family DNA polymerases of the DinB branch, including the human homolog Pol κ [22]. The DinB polymerases seem to have a special role in bypassing N 2 -dG lesions [38], with higher efficiency and accuracy than other DNA polymerases in cellular [39] and in vitro environments [40,41].…”
Section: Dpo4 Produces Mismatch and Frameshift Mutations At Bp-derivementioning
confidence: 98%
“…Although deletion of either gene does not alter the frequency of spontaneous mutation, 7,17 it results in an increase in the frequency of mutagenesis induced by certain DNA damaging agents. 11,20 Such behavior is analogously observed with respect to UV-induced mutation in human cells deficient in pol h function, which replicates relatively accurately over thymine-thymine cyclobutane dimers. 30,31 Substrate specificity also appears to be conserved between DinB and pol k. Both enzymes are able to bypass N 2 -B[a]P-adducted template G. 20,32,33 Moreover, they each display a striking 10-15 fold increased activity on a template N 2 -furfuryl-dG relative to undamaged DNA.…”
Section: Lesion Bypass Polymerases: a New Enzyme Superfamilymentioning
confidence: 49%
“…11,20 Such behavior is analogously observed with respect to UV-induced mutation in human cells deficient in pol h function, which replicates relatively accurately over thymine-thymine cyclobutane dimers. 30,31 Substrate specificity also appears to be conserved between DinB and pol k. Both enzymes are able to bypass N 2 -B[a]P-adducted template G. 20,32,33 Moreover, they each display a striking 10-15 fold increased activity on a template N 2 -furfuryl-dG relative to undamaged DNA. 11 Increased proficiency is also displayed by pol h replicating its cognate substrate T-T cyclobutane pyrimidine dimers.…”
Section: Lesion Bypass Polymerases: a New Enzyme Superfamilymentioning
confidence: 49%
See 1 more Smart Citation
“…Many in vitro studies have been carried out using different damaged DNA substrates, and it has been concluded that some of the polymerases are more effective at inserting nucleotides across from damaged bases but are unable to extend from the inserted nucleotide (eg polι), whereas others are less efficient at this insertion step but can extend from a nucleotide inserted by another polymerase opposite a damaged base. Both in vivo and in vitro studies have shown that polκ can carry out TLS past DNA containing benzo[a]pyrene -guanine adducts [12,13].…”
Section: Tls Polymerasesmentioning
confidence: 99%